2015
DOI: 10.3390/s150409360
|View full text |Cite
|
Sign up to set email alerts
|

Study of Multi-Armed Bandits for Energy Conservation in Cognitive Radio Sensor Networks

Abstract: Technological advances have led to the emergence of wireless sensor nodes in wireless networks. Sensor nodes are usually battery powered and hence have strict energy constraints. As a result, energy conservation is very important in the wireless sensor network protocol design and the limited power resources are the biggest challenge in wireless network channels. Link adaptation techniques improve the link quality by adjusting medium access control (MAC) parameters such as frame size, data rate, and sleep time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…7 Interestingly, spectral selection may effectively improve the transmission performance of a neighbor sensor node. 4 The distributed subcarriers and power control algorithms aim to minimize the power consumption of each bit information from subcarriers, 8,9 and the simulation results demonstrated that the performance of the proposed approach is close to that of the centralized optimal solution. However, the authors only considered the data transmission rate and power consumption of a neighbor sensor node and disregarded the performance of the entire route.…”
Section: Introductionmentioning
confidence: 94%
“…7 Interestingly, spectral selection may effectively improve the transmission performance of a neighbor sensor node. 4 The distributed subcarriers and power control algorithms aim to minimize the power consumption of each bit information from subcarriers, 8,9 and the simulation results demonstrated that the performance of the proposed approach is close to that of the centralized optimal solution. However, the authors only considered the data transmission rate and power consumption of a neighbor sensor node and disregarded the performance of the entire route.…”
Section: Introductionmentioning
confidence: 94%
“…Much research has been conducted in the area of computing the optimal communication-channel parameters used by IoT end nodes and the network server [12], [13], [14], [15]. The work has been especially focused on optimizing energy requirements of end nodes [16], [17], [18], [19], [20], selecting a communication channel [21], [22], [23], reducing the number of collisions [24], [25], [26], predicting collisions [27], or making the communication generally more efficient [28], [29], [10].…”
Section: Related Workmentioning
confidence: 99%